2020
DOI: 10.3390/ijerph17186815
|View full text |Cite
|
Sign up to set email alerts
|

WHIRL Study: Workplace Health Interprofessional Learning in the Construction Industry

Abstract: Interprofessional learning (IPL) is essential to prepare healthcare trainees as the future public health workforce. WHIRL (Workplace Health InteRprofessional Learning) was an innovative IPL intervention that engaged volunteer healthcare trainees (n = 20) in multi-professional teams to deliver health checks (n = 464), including tailored advice and signposting, to employees in the UK construction industry (across 21 events, 16 sites, 10 organisations) as part of an ongoing research programme called Test@Work. Vo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 50 publications
0
9
0
4
Order By: Relevance
“…Outros cenários foram apresentados pelos estudos elencados nesta revisão, como treinamento de profissionais atuantes em centros especializados no tratamento de cânceres (Phipps et al, 2018), especialidade médica em ultrassonografia (Smith et al, 2018), pós-graduação e pesquisa biomédica (Lewis, Martina, McDermott, Chaudron, et al, 2017), residência médica em Medicina de Família e Comunidade (Prunuske et al, 2019), serviços de saúde com atendimento de clínica médica e medicina do trabalho (Blake et al, 2020) e, por fim, em programas de assistência à saúde e imunização (Hossain et al, 2021).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Outros cenários foram apresentados pelos estudos elencados nesta revisão, como treinamento de profissionais atuantes em centros especializados no tratamento de cânceres (Phipps et al, 2018), especialidade médica em ultrassonografia (Smith et al, 2018), pós-graduação e pesquisa biomédica (Lewis, Martina, McDermott, Chaudron, et al, 2017), residência médica em Medicina de Família e Comunidade (Prunuske et al, 2019), serviços de saúde com atendimento de clínica médica e medicina do trabalho (Blake et al, 2020) e, por fim, em programas de assistência à saúde e imunização (Hossain et al, 2021).…”
Section: Discussionunclassified
“…A aprendizagem interprofissional tem um papel inovador em ambientes de trabalho, uma vez que proporciona uma troca de diferentes experiências profissionais (Blake et al, 2020). Os mesmos autores observaram o crescimento acadêmico e profissional de estudantes da área da saúde, ao vivenciarem as nuances do "mundo real" em um serviço de promoção à saúde.…”
Section: Discussionunclassified
“…The intervention was an optional one-off individual health check with tailored health advice and signposting, offered to the construction workforce in health check events delivered as part of the Test@Work program [ 32 ]. The events were undertaken at 10 participating organizations across 16 construction sites.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were provided with personal individualized feedback on their health check results; they received tailored health advice and signposting and were provided with a take-away health resource pack. The rationale, content, and delivery of the health checks and health advice is described in detail elsewhere, together with further details about the delivery team and their training [ 32 ]. Line managers at the participating organizations were provided with an evidence-based digital toolkit about the rationale for workplace health promotion and health screening, with details about the processes for HIV testing [ 33 ] to support the promotion of the event to their staff.…”
Section: Methodsmentioning
confidence: 99%
“…Recruitment to the study took place at one of 21 workplace health check events between August 2019 to February 2020 at the participating organisations. The health check events were delivered as part of a wider research programme called Test@Work; further details on site recruitment, health checks and study findings are therefore reported elsewhere [ 53 ]. Here, the events were simply used as a platform to access employees in the construction industry and recruit employees into ‘Test@Work Texts’ (a follow-on workplace text messaging study conducted during the COVID-19 pandemic).…”
Section: Methodsmentioning
confidence: 99%